Efektivitas Penyuluhan Pupuk dan Pemupukan Dikelompok Tani Wanita Cerdas di Desa Lawelu Kec Ulumoro'o, Kab. Nias Barat - Intan Novibriani Zendrato; Oferlina Harefa; Ardianus Berkat Saleh Waruwu; Helmin Parida Zebua (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
This research aims to evaluate the effectiveness of fertilizer extension and fertilization in the women's farmer group "Cerdas" in Lawelu Village, Ulumoro'o District, West Nias Regency. The research method used a quantitative approach with data collection techniques through observation, structured interviews, and questionnaires. The results showed that 75% of respondents experienced an increase in understanding of fertilizer types, doses, and application times after counseling. However, implementation in the field is still constrained by limited access to subsidized fertilizer (60% of respondents). The conclusion of this study states that extension is effective in improving knowledge but requires policy support to improve fertilizer accessibility.